Nonlinear seismic performance of a 12th century historical masonry bridge under different earthquake levels - Karaton, Muhammet; Aksoy, H. Suha; Sayin, Erkut; Calayir, Yusuf (Pergamon-Elsevier Science Ltd, 2017)
In construction of historical masonry structures, only static loads were generally taken into account. Therefore, these structures may be damaged or ruined due to seismic effects. Earthquake performances of historical masonry structures must be obtained for carrying to the future and the preservation of them. In this study, nonlinear seismic responses of Malabadi Bridge, built in 12th century, are evaluated. The main span of the bridge is 38.6 m and it is the widest of all stone arch bridges existing in Anatolia. Three different earthquake levels (D1, D2 and D3) are selected for seismic loading. Synthetic acceleration data are produced by considering seismic characteristics of the region. For determining the material properties of the bridge, uniaxial compressive strength tests, ultrasound tests, Schmidt hammer tests and mass loss tests are conducted. Homogenized material properties for macro modelling technique are obtained by using the test results. A smeared crack model which includes tensile cracking and compressive crushing effect is selected for the masonry material. Drucker-Prager material model is also used for the backfill material. No damage region is obtained at arches and spandrel walls under the D1 and D2 earthquake loadings. However, plastic deformations are observed at backfill material under D2 earthquake loadings. Numerical results are showed that the main arch of the bridge have heavily damaged under D3 earthquake loading.
Keywords: Historical masonry bridge; Material properties; Macro modelling; Nonlinear seismic response